ANALISIS PENGARUH PERILAKU KONSUMEN DAN LINGKUNGAN PEMASARAN TERHADAP KEPUASAN PELANGGAN PADA GRAPARIKIOS TELKOMSEL KOMPLEK SETIA BUDI MEDAN. - debby c.d; beby K F sembiring (Jurnal Media Informasi Manajemen, 2013)
Abstract : This research target is to know and analyse the influence Consumer Behaviour and Marketing Environtmental to Customer Satisfaction Graparikios  Komplek Setia Budi Medan. Population in this research is all customers of at office of to 88 employee people. Sample in this research use the aksidental sample method consisted of 88 coustomer of office Graparikios Medan Komplek Setia Budi. This collection of primary through questionnaire, which before the questionnaire distributed first tasted the validity and reliability for questionnaires to 88 customers people Graparikios Medan komplek Setia Budi. Primary data were collected by distributing questionnaires, which prior to the questionnaire distributed first tested the validity and reliability of the 30 people Graparikios subscribers Telkomsel Medan Komplek Setia Budi. The method of analysis used in this research in descriptive analysis method and quantitative analysis that is with the double linear regression analysis. Result of research indicate that the consumer behaviour and marketing environmental have an effect on positively and significant to Customer Satisfaction of at office of coustomer Graparikios Komplek setia Budi Medan.Kata kunci : perilaku konsumen, lingkungan pemasaran dan kepuasan  pelanggan